Trial protocol for SiroSkin: a randomised double-blind placebo-controlled trial of topical sirolimus in chemoprevention of facial squamous cell carcinomas in solid organ transplant recipients - Lea Dousset; Daniel C. Chambers; Angela Webster; Nicole Isbel; Scott Campbell; Carla Duarte; Louisa Collins; Diona Damian; Anne Tseng; Emma Karlsen; Olga Victoria Ilinsky; Susan Brown; et al. (Trials, 2024)
Abstract Background Keratinocyte carcinomas such as basal cell carcinomas and squamous cell carcinomas are a major burden affecting morbidity and mortality in solid organ transplant recipients (SOTRs). Best treatment includes frequent skin checks for early detection and surgery for high incidence of skin cancers. Sirolimus is an immunosuppressive drug which may reduce the burden of skin cancer but may be poorly tolerated when given orally. Topical sirolimus has been proven effective at reducing the burden of skin cancers in animal models, and its safety has long been established in children with tuberous sclerosis. A recent 12-week phase II trial of topical sirolimus suggested it was safe and effective at reducing the early signs of skin cancer in the absence of major side effects. The aim of the SiroSkin trial is to determine whether topical sirolimus can fill a major gap in current therapies by reducing the onset and number of new skin cancers thus reducing burden of disease and cost-effectiveness. Methods Protocol for a multi-centred phase III, participant- and clinician assessor-blinded, placebo-controlled randomised trial in SOTRs. A minimum 146 participants randomised 1:1 will be treated with 1% topical sirolimus versus placebo applied to the face on a regular basis for 24 weeks. Participation is 24 months in total—24 weeks of treatment and 18 months of follow-up. Outcomes include the number of keratinocyte carcinomas at 24 weeks of treatment compared to placebo and then at 12 and 24 months after initiation of treatment. Analysis will be as per protocol and intention to treat. Discussion The results of this trial will inform management strategies for skin cancers in SOTRs and provide evidence for cost-effectiveness. Trial registration Clinicaltrials.gov NCT05860881. Registered on June 15, 2023, and on anzctr.org.au (registration number NCT05860881).